Effectiveness of a Novel Smartphone Health Education Intervention in Enhancing Knowledge, Attitudes, and Practices for the Prevention of Respiratory Tract Infections Among Private Hajj Pilgrims From Malaysia - Goni, Mohammed Dauda; Naing, Nyi Nyi; Hasan, Habsah; Wan-Arfah, Nadiah; Deris, Zakuan Zainy; Arifin, Wan Nor; Baaba, Aisha Abubakar; Adam, Babagana Mohammed; Arshad, Muhammad Rafie (Frontiers in Public Health, 2021)
This study was aimed to develop and evaluate the efficacy of a health education program for increasing knowledge, changing attitudes and promoting prevention practices to reduce the incidence of respiratory tract infections (RTIs) among Malaysian Hajj pilgrims. A quasi-experimental study was done among 130 Hajj pilgrims attending Hajj orientation course organized by private Hajj tour companies. Hajj pilgrims assigned to intervention group (n = 65) and control group (n = 65). Data were collected baseline and after return from Hajj using a validated questionnaire. Mixed design repeated measure ANOVA was used to analyse the effect of group, time, and group-time interaction on the dependent variables. There were a significant improvement in knowledge, attitude and practice scores in the intervention group compared to the control group. Based on the findings of the interaction of time and group, there was a significant statistical difference for post-intervention for knowledge (p=0.005), attitude (p=0.041) and practice (p=0.002). Similarly, the occurrence of RTI in the intervention group is lower when compared to the control group. The newly-established health education intervention smartphone application was effective in improving KAP towards RTIs prevention among pilgrims.